Retinal Artery Occlusion Associated with Prepapillary Arterial Loop: An Isolated Ocular Disease? Case Report and Literature Review - Mansour AM; Parodi MB; Casella AMB; Kheir WJ; Bashshur ZF (Clinical Ophthalmology)
Ahmad M Mansour,1 Maurizio Battaglia Parodi,2 Antônio Marcelo Barbante Casella,3 Wajiha J Kheir,1 Ziad Fayez Bashshur1 1Department of Ophthalmology, American University of Beirut, Beirut, Lebanon; 2Department of Ophthalmology, University Vita-Salute Milan, Milan, Italy; 3Department of Ophthalmology, Universidade Estadual de Londrina, Paraná, BrazilCorrespondence: Ahmad M Mansour, Department of Ophthalmology, American University of Beirut, Beirut, Lebanon, Tel +961-337-7633, Email ammansourmd@gmail.comPurpose: When branch retinal artery occlusion is linked to prepapillary artery loop, is a systemic work-up necessary?Methods: Case Report and literature review. The databases searched were MEDLINE OVID, Scopus, Web of Science, and Embase. The search was for all relevant articles published from inception until October 31, 2024.Results: A total of 33 cases of prepapillary artery loop with retinal artery occlusion were reviewed. Median age at diagnosis was 24 years (range 10– 64). Twenty five cases had no systemic disease while 9 had unrelated systemic disorder. Systemic workup was carried in 17 cases and was negative. The location of the branch retinal artery occlusion was inferior in 21 cases, superior in 6 cases, and combined superior and inferior in 2 cases. Paracentral acute middle maculopathy was noted in 2 cases. Precipitating factors included exercise in 4 cases, head trauma in 2 cases, blunt ocular trauma, severe sneezing, ocular rubbing and sun exposure in 1 case each.Conclusion: A branch retinal artery occlusion linked to a prepapillary loop appears as a distinct ocular condition in young healthy individuals. There is no definite need for additional diagnostic testing in such patients with a negative systemic history.Keywords: prepapillary arterial loop, branch retinal artery occlusion, systemic workup